Anti-diabetic properties of traditional herbal concoction containing Eleutherine palmifolia (L.) Merr., Momordica charantia L., and Syzygium polyanthum (Wight.): a bibliometric analysis - Muhammad Afnan Shakir Hairani; Fadzilah Adibah Abdul Majid; Nor Hafizah Zakaria; Dwi Hudiyanti; Anis Fadhlina; Hassan Ibrahim Sheikh (Food Production, Processing and Nutrition)
Abstract Eleutherine palmifolia, Momordica charantia, and Syzygium polyanthum are herbal plants, traditionally used as natural remedies for diabetes. There have been numerous articles published on the anti-diabetic efficacy of these plants; yet, no bibliometric study on the subject is available. In this study, the published papers on the utilization of E. palmifolia, M. charantia, and S. polyanthum as anti-diabetic agents were examined using bibliometric approach, focusing on countries, organizations, authors, and keywords. The phytochemicals, pharmacological properties, and mechanism of action of each herbal plant associated with diabetes were also discussed in detail. The data were searched through the SCOPUS database and bibliometric analysis was performed using VOSviewer software. The World Flora Online (WFO) was used to confirm the identity of the plant species. A total of 1008 articles were retrieved with M. charantia (977 articles) showing the highest number of publishing articles compared to E. palmifolia (9 articles), and S. polyanthum (22 articles). Upon further review of these plants, the findings showed that each plant has active ingredients that can prevent as well as control the complications of diabetes. Eleutherol, eleuthenone, eleutherinoside A, kuguacin, momordicin, vicine, squalene, myricitrin and epigallocatechin gallate (EGCG) were among the phytochemicals responsible for the effect. The possible underlying mechanisms of action were attributed to lowering blood glucose, increasing insulin production, inhibiting intestinal glucose absorption, and enhancing glucose uptake by the muscles. Based on the review, it is evidenced that the individual plants demonstrated a promising anti-diabetic activity, thus, it is recommended to conduct further studies using a polyherbal mixture, combining these three extracts and analyzing using in vitro and in vivo models. Graphical Abstract